2016
DOI: 10.1377/hlthaff.2015.1031
|View full text |Cite
|
Sign up to set email alerts
|

Adding A Measure Of Patient Self-Management Capability To Risk Assessment Can Improve Prediction Of High Costs

Abstract: We explored whether supplementing a clinical risk score with a behavioral measure could improve targeting of the patients most in need of supports that reduce their risk of costly service utilization. Using data from a large health system that determines patient self-management capability using the Patient Activation Measure, we examined utilization of hospital and emergency department care by the 15 percent of patients with the highest clinical risk scores. After controlling for risk scores and placing patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 13 publications
0
42
0
1
Order By: Relevance
“…Assessment of patient activation over time permits an early identification of patients in whom a change in activation levels may flag a change in health status. Moreover, longitudinal PAM data can be used to develop risk prediction models that predict adverse patient outcomes . Another apparent limitation was the modest response rate of 38.5%, which is, however, comparable to other studies in people with diabetes .…”
Section: Discussionmentioning
confidence: 93%
“…Assessment of patient activation over time permits an early identification of patients in whom a change in activation levels may flag a change in health status. Moreover, longitudinal PAM data can be used to develop risk prediction models that predict adverse patient outcomes . Another apparent limitation was the modest response rate of 38.5%, which is, however, comparable to other studies in people with diabetes .…”
Section: Discussionmentioning
confidence: 93%
“…Patient engagement measures have the potential to drive changes in how the healthcare system is organized and delivered and might contribute to actually realize the “patient engagement promise.” Moreover, patient engagement measurements—initially developed for use in research (Hibbard et al, 2005; Graffigna and Barello, 2016)—have recently started to be considered a mandatory requirement for health professionals to enhance clinical management (Graffigna and Barello, 2016; Hibbard et al, 2016). Adopting this view also implies to consider that patients' engagement expectations might vary depending of the phase of the patients' medical journey (Barello et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite resistances to their adoption still exist, clinicians increasingly recognize the benefits of collecting their patients' engagement expectations. Particularly, the call for patient engagement measures adoption has been sustained by evidences that show they can be of benefit for multiple purposes (Simmons et al, 2014; Graffigna and Barello, 2016; Hibbard et al, 2016; Roberts et al, 2016): (1) a process or outcome measure to determine the patients' characteristics that may predict their level of engagement and their risk for dis-engagement, (2) a tool to personalized interventions based on the individual's ability for self-management (3) an outcome measure for evaluating the performance and effectiveness of healthcare interventions, comparing pre- to post-intervention assessments of one patient's level of engagement; (4) an instrument to optimize and tailor professionals' relational and communicational strategies and, potentially, to improve the effectiveness of their actions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, investigators have reported that the factors associated with high levels of activation for SM, both within the general population and for those living with multiple chronic conditions, were female gender, 20 younger age, 21 higher level of education, 21 greater self-care knowledge and support, 22 adequate physical functioning, 21 and lower disease severity (including both primary disease and comorbidities). 23,24 Whether these factors impact the mediation pathway between self-efficacy, patient activation, and SM behaviors in HF patients is unknown. Therefore, we explored moderators of the mediation pathway in order to establish for whom the mediating effects of patient activation were strongest.…”
Section: Introductionmentioning
confidence: 99%